2016
DOI: 10.20289/zfdergi.390271
|View full text |Cite
|
Sign up to set email alerts
|

Economic Analysis of Pesticide Use on Grape Growing: A Case Study for Manisa-Turkey

Abstract: Turkey have been trying to decrease pesticide residues in vegetables and fruits. There is firstly a growing desire to reduce pesticide usage in vineyards to decrease the risk of pesticide residues. Today, farm-level costs include the costs of the pesticides, and their application. This study was conducted to analyse the farmlevel economics of pesticide use on grape growing in a selected regions from Turkey. Data was collected from 72 grape farmers. According to&… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 12 publications
1
14
0
Order By: Relevance
“…Measuring the time spent during agricultural operations in the parcel was performed with the aid of chronometer (Sonmete 2006). In Kocturk and Engindeniz (2009) reported that, "The input energy is also classified into direct and indirect, and renewable and non-renewable forms. The indirect energy consists of pesticide and fertilizer, while the direct energy includes human and animal labour, diesel and electricity used during the production process.…”
Section: Methodsmentioning
confidence: 99%
“…Measuring the time spent during agricultural operations in the parcel was performed with the aid of chronometer (Sonmete 2006). In Kocturk and Engindeniz (2009) reported that, "The input energy is also classified into direct and indirect, and renewable and non-renewable forms. The indirect energy consists of pesticide and fertilizer, while the direct energy includes human and animal labour, diesel and electricity used during the production process.…”
Section: Methodsmentioning
confidence: 99%
“…These indices/indicators are widely used in scientific and research discussions about the water–energy nexus in irrigation and crop production systems (e.g. Bos et al , ; Khan et al , ; Koctürk and Engindeniz, ; Pereira, , and others).…”
Section: Discussionmentioning
confidence: 99%
“…Guar and lupin energy input-output have been done and the computations have been given in Table 2. Kocturk and Engindeniz (2009) reported that; "The input energy can also be classified into direct, indirect, renewable and non-renewable forms (Mandal et al, 2002;Singh et al, 2003)". Energy usage efficiency computations in guar and lupin production have been given in Table 3.…”
Section: Methodsmentioning
confidence: 99%
“…Several researches have been done on wheat, corn and other plant's energy usage efficiency in agricultural production. Some of these researches may be listed as those on the energy usage researches of corn (Ozturk et al, 2006), maize (Vural and Efecan, 2012), canola (Unakitan et al, 2010), soybean (Mandal et al, 2002), wheat (Marakoglu and Carman, 2010;Tipi et al, 2009), sesame (Akpinar et al, 2009), potato (Mohammadi et al, 2008), barley (Mobtaker et al, 2010), grape (Kocturk and Engindeniz, 2009), sugar beet (Haciseferogullari et al, 2003), sunflower (Davoodi andHoushyar, 2009), barley (Azizi andBaran and Gokdogan, 2014), corn silage etc. This study does not contain any research regarding the energy input-output analysis of guar and lupin production in Turkey.…”
Section: Introductionmentioning
confidence: 99%